KESADARAN MEREK CRISP ENYE-ENYE - Mutia Khoerunisa, (2020)
Based on data from popular brands of snacks made from cassava in Banten Province in 2019, Crisp Enye-Enye is in 11th position out of 14 popular brands. This means brand awareness of Crisp Enye-Enye is still low. So it is indicated that there are problems related to brand awareness. Therefore, this study goals to evaluated and show whether there is an influence between advertising, direct marketing, and personal selling on brand awareness. This research method is quantitative descriptive with Crisp Enye-Enye consumer population spread in DKI Jakarta Province, Lebak Regency, and Tangerang Regency were 80 respondents. The data analysis system used is descriptive analysis and inferential analysis with the SmartPLS analysis tool version 3.2.7. The results of this study indicate the Adjusted R Square value of 73,1%. Hypothesis test results show that advertising variables affect brand awareness with a path coefficient of 0.351. Direct marketing variables affect brand awareness with a path coefficient of 0.416, while personal sales do not affect brand awareness with a path coefficient result of 0.174.